Access to justice for Ethiopian migrant domestic workers: unveiling legal, structural, and gendered violence in Lebanon - Banchi Yimer; Tsigereda Birhanu; Francisca Ankrah; Debora Asfaw; Omar Taleb; Jasmin Lilian Diab (Frontiers in Sociology)
This study investigates the barriers to legal access faced by Ethiopian migrant domestic workers (MDWs) in Lebanon, highlighting the legal violations they endure. The research encompasses all phases of criminal cases, from initial investigations to trial and verdict issuance. Utilizing a diverse methodology, the study draws on a sample of judgments from Egna Legna Besidet's Legal Program, qualitative interviews with 66 Ethiopian MDWs, and insights from 10 key informants and five legal experts. Ethical considerations, including a trauma-informed approach and thorough anonymization, were paramount. Findings reveal that MDWs encounter systemic injustices and insurmountable barriers within the Lebanese legal system, exacerbated by societal prejudices, exorbitant recruitment fees, language barriers, and limited legal awareness. The Kafala sponsorship system and restrictive immigration policies further hinder their legal navigation. Discriminatory attitudes, lack of legal safeguards, and inadequate support from embassies and consulates perpetuate a cycle of exploitation and abuse. The initial investigation stage is fraught with coercion and procedural violations, while trials and verdicts often lack fairness and adequate evidence. The study calls for comprehensive legal reforms, better enforcement of existing laws, accessible information, legal aid, and multi-stakeholder collaboration to dismantle these barriers and ensure justice for MDWs.